The splendid and the vile ebook A saga of churchill, family, and defiance during the blitz. - Larson, Erik (2020)
#1  NEW YORK TIMES  BESTSELLER • The author of  The Devil in the White City  and  Dead Wake  delivers an intimate chronicle of Winston Churchill and London during the Blitz—an inspiring portrait of courage and leadership in a time of unprecedented crisis   “One of [Erik Larson’s] best books yet . . . perfectly timed for the moment.”— Time  •  “A bravura performance by one of America’s greatest storytellers.”—NPR     NAMED ONE OF THE BEST BOOKS OF THE YEAR BY The New York Times Book Review • Time • Vogue • NPR •  The Washington Post • Chicago Tribune • The Globe & Mail • Fortune • Bloomberg • New York Post •  The New York Public Library • Kirkus Reviews  • LibraryReads • PopMatters On Winston Churchill’s first day as prime minister, Adolf Hitler invaded Holland and Belgium. Poland and Czechoslovakia had already fallen, and the Dunkirk evacuation was just two weeks away. For the next twelve months, Hitler would wage a relentless bombing campaign, killing 45,000 Britons. It was up to Churchill to hold his country together and persuade President Franklin Roosevelt that Britain was a worthy ally—and willing to fight to the end. In The Splendid and the Vile , Erik Larson shows, in cinematic detail, how Churchill taught the British people “the art of being fearless.” It is a story of political brinkmanship, but it’s also an intimate domestic drama, set against the backdrop of Churchill’s prime-ministerial country home, Chequers; his wartime retreat, Ditchley, where he and his entourage go when the moon is brightest and the bombing threat is highest; and of course 10 Downing Street in London. Drawing on diaries, original archival documents, and once-secret intelligence reports—some released only recently—Larson provides a new lens on London’s darkest year through the day-to-day experience of Churchill and his family: his wife, Clementine; their youngest daughter, Mary, who chafes against her parents’ wartime protectiveness; their son, Randolph, and his beautiful, unhappy wife, Pamela; Pamela’s illicit lover, a dashing American emissary; and the advisers in Churchill’s “Secret Circle,” to whom he turns in the hardest moments.   The Splendid and the Vile  takes readers out of today’s political dysfunction and back to a time of true leadership, when, in the face of unrelenting horror, Churchill’s eloquence, courage, and perseverance bound a country, and a family, together.